Dos levantes de Castela às revoluções comuneras do Paraguai : apropriações e ressignificações de um conceito em três atos - Cerveira, Luís Alexandre (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation has as its objective to understand the appropriations and resignifications that were made of the comunero concept, employees for the first time in comuneros revolts de Castile (1520-1522) by different social actors involved in the rebel uprisings that took place in Colonial Paraguay. For this, we reconstitute and analyze the process of the three revolts that have been referred to as comuneros movements by historiography grounded in the presupposed theoretical methodological assumptions of Quentin Skinner and Michel de Certeau, we question this consolidated and widespread interpretation.
Keywords: Paraguai; Comuneros; Ressignificações; Apropriações; Historiografia; Paraguay; Resignifications; Appropriations; Historiography; ACCNPQ::Ciências Humanas::História